Prevalence and clinical pattern of paediatric HIV infection at the University College Hospital, Ibadan, Nigeria: a prospective cross-sectional study - Oladokun Regina E; Ogunbosi Babatunde O; Brown Biobele J; Osinusi Kikelomo I (Italian Journal of Pediatrics, 2011)
Abstract Background The prevalence of Paediatric HIV infection is largely unknown in many countries in sub-Saharan Africa. This study was aimed at determining the prevalence, clinical pattern of HIV infection and outcome among new patients aged <15 years using age-specific diagnostic methods. Methods A prospective cross sectional study was carried out using the provider initiated HIV testing and counselling (PITC) model. HIV rapid test in parallel was used for screening and confirmation was with HIV DNA PCR in children <18 months and Western Blot in children ≥ 18 months. Results A total of 600 children were enrolled with ages ranging between one day and 179 months. Male: female ratio was 1.2:1. HIV seroprevalence was 12.3% and after confirmatory tests, the prevalence was 10%. Fourteen (37.8%) of the children aged less 18 months were exposed but not infected. Mother-to-child transmission accounted for 93.3% of cases. Features predictive of HIV infection were diarrhoea, cough, weight loss, ear discharge generalized lymphadenopathy, presence of skin lesions, parotid swelling and oral thrush. About 75% presented in advanced or severe clinical stages of the disease, 56.8% had severe immunodeficiency while 50% had viral loads more than 100,000 copies/ml. Mortality rate was 14.3% among HIV positive compared with 11.3% in HIV negative children but was not significant. Among the HIV positive children, 26.7% were orphans. Conclusions The prevalence rate of HIV infection among new patients screened using the PITC model was high, majority resulting from mother-to-child transmission. Most children presented in advanced stages of the disease and mortality rate among them was high. Though, the study site being a referral centre might have contributed to the high prevalence observed in this study, there is a need to expand access to PMTCT services, ensure implementation of PITC in paediatric settings and expand support services for HIV infected children.